2018
DOI: 10.1016/j.athoracsur.2018.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Detachment in Ventricular Septal Defect Closure Does Not Impact Valve Function

Abstract: TVD did not compromise long-term valve durability and did not impose increased morbidity. Patients who underwent TVD had a similar prevalence of mild TR to patients without TVD. Moderate TR was exceptionally rare in both groups. When exposure is difficult, TVD is a safe and effective technical adjunct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In the advancing years, further variants TVD consisting of septal leaflet detachment have also been described in the pediatric literature (8)(9)(10). Moreover, circumferential detachment of the septal or anterior leaflets, longitudinal incision of the septal leaflet, subvalvular tricuspid apparatus detachment (chordae papillary muscle or both) from septum have all been described in prior reports examining the tricuspid valve dysfunction at short term follow up (11).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the advancing years, further variants TVD consisting of septal leaflet detachment have also been described in the pediatric literature (8)(9)(10). Moreover, circumferential detachment of the septal or anterior leaflets, longitudinal incision of the septal leaflet, subvalvular tricuspid apparatus detachment (chordae papillary muscle or both) from septum have all been described in prior reports examining the tricuspid valve dysfunction at short term follow up (11).…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies indicate different results. Fraser et al (11) and Pourmoghadam et al (14) measured a significant increment in both CPB time and X-clamping time. On the other side, Gaynor et al (9) and Russell et al (10) reported no differences between TVD or non-TVD performed groups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Conventionally, open-heart surgical repair through midline sternotomy and cardiopulmonary bypass (CPB) is the primary approach for many years (7) . Surgical VSD closure commonly performed through the right atrial approach in which the VSD is reached through the tricuspid valve (8) . The interventricular septum is typically closed by using an autologous pericardium patch, which is fixed by either interrupted or continuous suturing techniques depending on the surgeon preference (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Severe pulmonary arterial hypertension (PAH) may lead to increased risk of morbidity and death in individuals with big ventricular septal defects (VSD) if the VSD is closed. [2] If VSD is moderate to big and non-restrictive, the closure of VSDs is advised before the age of six months to avoid pulmonary vascular disease. Cardiac catheterization is suggested for measuring pulmonary vascular resistance and testing pulmonary vasoreactivity, in particular if the permanent increase in pulmonary vascular resistance is a clinical issue.…”
Section: Introductionmentioning
confidence: 99%